Disparity in use of modern combination chemotherapy associated with facility type influences survival of 2655 patients with advanced pancreatic cancer. (4th March 2022) - Ladekarl, Morten; Rasmussen, Louise Skau; Kirkegård, Jakob; Chen, Inna; Pfeiffer, Per; Weber, Britta; Skuladottir, Halla; Østerlind, Kell; Larsen, Jim Stenfatt; Mortensen, Frank Viborg; Engberg, Henriette; Møller, Henrik; et al.
Abstract: Aim: Academic and high volume hospitals have better outcome for pancreatic cancer (PC) surgery, but there are no reports on oncological treatment. We aimed to determine the influence of facility types on overall survival (OS) after treatment with chemotherapy for inoperable PC. Material and methods: 2, 657 patients were treated in Denmark from 2012 to 2018 and registered in the Danish Pancreatic Cancer Database. Facilities were classified as either secondary oncological units or comprehensive, tertiary referral cancer centers. Results: The average yearly number of patients seen at the four tertiary facilities was 71, and 31 at the four secondary facilities. Patients at secondary facilities were older, more frequently had severe comorbidity and lived in non-urban municipalities. As compared to combination chemotherapy, monotherapy with gemcitabine was used more often (59%) in secondary facilities than in tertiary (34%). The unadjusted median OS was 7.7 months at tertiary and 6.1 months at secondary facilities. The adjusted hazard ratio (HR) of 1.16 (confidence interval 1.07–1.27) demonstrated an excess risk of death for patients treated at secondary facilities, which disappeared when taking type of chemotherapy used into account. Hence, more use of combination chemotherapy was associated with the observed improved OS of patients treated at tertiary facilities. Declining HR's per year of first treatment indicated improved outcomes with time, however the difference among facility types remained significant. Discussion: Equal access to modern combination chemotherapy at all facilities on a national level is essential to ensure equality in treatment results.